Family Reunification and the Transnational Family - Clancy, Kathlin (Université d'Ottawa | University of Ottawa, 2014)
In an age of increased global flows and knowledge sharing across borders, is state migration policy restricting opportunities and causing harm by grounding people, often away from their families, to one particular state or region? Discussion of family reunification in countries of net immigration such as Canada, Australia, and the EU nations often pits state interests against individual rights, including the right to the family. But are states and transnational families necessarily at odds, and if so, then does this always need to be the case? This research paper first identifies a series of state goals which, at first glance, appear to be divergent from the mobility of families. However, the paper then describes opportunities to align these state interests with individual rights, notably the right to the family. The result is a 12-part framework, in table form, that for the first time analyzes and demonstrates how existing state goals – that are currently used to justify the restriction of family reunification – could in fact best be enhanced through an increase in family reunification, within a reimagined citizenship regime that gives freedom to and gains from transnational families’ agency and resilience.